Prevention of Hamstring Injuries in Elite Football Players: Exercise and Load Management Strategies - Donggi Kim; Minchul Lee (운동과학)
PURPOSE Hamstring injuries are the most prevalent injuries among elite football players. Despite extensive research on hamstring injury prevention, the incidence of hamstring injuries continues to rise. This study aimed to provide a comprehensive overview of hamstring injuries and propose evidence-based management strategies for effective injury prevention in elite football environments. METHODS Information on the characteristics, mechanisms, risk factors, diagnosis, classification, and prognosis of hamstring injuries, and methods for exercise and load management related to injury prevention were obtained. Data were collected and analyzed from a variety of online databases and search engines, including PubMed, Web of Science, and Google Scholar. RESULTS In elite football, hamstring injuries predominantly occur during sprinting, with the long head of the biceps femoris being the most commonly affected muscle. This muscle is particularly vulnerable during the terminal swing phase of sprinting. Based on these characteristics, this study explored injury prevention strategies. The effectiveness of the Nordic hamstring curl (NHE), which is widely recognized as a preventive exercise for hamstring injuries, was critically reviewed. Additionally, effective injury prevention exercises and load management strategies have been proposed. Additionally, the acute–chronic workload ratio (ACWR), incorporates multiple internal and external load metrics beyond the Rating of Perceived Exertion (sRPE), enabling more precise load management. CONCLUSIONS This study investigated the importance of exercise and load management strategies for hamstring injury prevention in elite football players. Our findings suggest that eccentric hamstring strength training with high sprint specificity is most effective, with sprint training being the optimal exercise. Future research should compare hamstring injury prevention programs and establish a standardized ACWR framework to enhance these strategies.